External causes of mortality in Ukraine: standardized risks and lost profit - Kartashova, S.S.; Kaneva, T.V.; Omelchenko, E.M.; Polka, O.O. (Environment & Health, 2018)
Background: By the level of mortality of the external causes, Ukraine passes ahead of the countries of the European Union more than twice. The role of the external causes in our state is underestimated and insufficiently taken into account in the determination of the priorities of the policy directed to the reduction of the mortality and the increase of lifetime. Objective: We determined the demographic and socio-economic losses of the state through external causes of death (ICD-10: V01-Y98), including their individual nosologies (ICD-10: X45, V01-V99, X60-X84). Materials and methods: The data of the system of national accounts, forms of state statistical records: f. P-8 "Distribution of the deceased by sex, age groups, and causes of death" and f. A-1 - "General results of natural movement" and on the significance of the NBU discount rate of the Ministry of Finance were used as the sources of primary information. Results and conclusions: According to the classical structure of mortality, the external causes occupy the third ranked position after diseases of circulatory system and neoplasms while by the parameter of the YPLL (Years of Potential Life Lost) - the second one, and at this time their share increased 3.7 times. The latter is because the average age of the dead of the external causes is smaller by a factor of 1.9 than those who died of the circulatory system diseases. Among all external causes of death, special attention should be given to the accidents, the accidental poisoning, and the effects of alcohol, suicides: their share among external causes is ≈ 50%. At the analysis and assessment of the structural changes in the class of the external causes, an increase in the share of suicides in 2009-2016 was detected among both the female (by 42.2 ± 1.2%) and the male one (by 37.1 ± 0.8%) population. Performed ranking of the regions of the state in terms of relative risk established the territories of increased risk both for all external causes of death and individual nosologies (accidents, suicides, accidental poisoning and the effects of alcohol). Reduction of the risk of death of those causes to the average state would save about 7 thousand persons while the lost profit of the state would exceed 14 billion UAH only in 2015 – 2016.